Interdisciplinary dialogues on organizational paradox : investigating social structures and human expression - Bednarek, Rebecca (Research in the sociology of organizations ;, 2021)
Interdisciplinary Dialogues on Organizational Paradox is a two-part volume exploring how paradox theory benefits from interdisciplinary theorizing and how we might go about undertaking such research. The chapters draw from four disciplinary realms: beliefs, physicality, expression, and social structure. Unique commentaries from thought leaders expand and assess the focal pieces of each volume. Part B: Investigating Social Structures and Human Expression continues the exploration of the why, how and where of interdisciplinary research within paradox theory by looking specifically at the realms of social structure - from logic and Luhmann, to historical analysis - and expression - from linguistics, to the maths and poetry of Spencer-Brown, to jazz. The chapters are complemented with reflective commentaries from Charles Hampden-Turner and Ann Langley. The collection ends with an examination of where the interdisciplinary foundations for organizational paradox theory arose via conversations with seminal paradox scholars.